Synthesis and Characterisation of Bismuth Oxide Powders - Mhamat Nasudin, Noorfarizan Nasriah (2005)
Bismuth oxide has found application in various areas including medicine, material synthesis, organic synthesis and catalysis. In catalysis, this single oxide found important role in providing oxygen for the a-hydrogen abstraction of propene to produce acrolein and acrylonitrile via oxidation and amrnoxidation process. This study investigates the influence of multitude of synthesis parameters (precipitating agent, concentration and aging process) on the formation of bismuth oxide powders. The samples microstructural properties were determined using a variety of techniques such as X-Ray Diffraction (XRD), BET Surface Area Measurement, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) Spectroscopy. Extend of reduction of the oxide was also investigated by employing Temperature Programmed Reduction (TPR) technique. Finally, a Temperature Programmed Reaction (TPRn) was conducted on selected samples to determine the surface intermediates.On the influence of precipitating agent, a-Bi203 that were produced via NaOH as a precipitating agent and calcined in air were discerned to exhibit higher surface areas and higher intrinsic activity as compared to P-Bi203 which is produced by using NH40H as a precipitating agent. However, increment in NaOH concentration has induced the formation of low surface area material. Investigation on the influence of bismuth concentration on the formation of final products gave high surface area powders with high oxide reducibility when using low concentration of bismuth. The sample high surface area property with its corresponding small particle size has been evidenced to be an induction factor to enhance the oxygen reducibility of the samples. Study on the effect of aging process showed that the parameters controlled the powders particle size. Temperature programmed reaction studies of propane oxidation showed that a- Bi203 gave the higher percentage of selectivity to propene and acrolein when compared to P-Bi203. The reaction was found to be in step-wise mechanism through the formation of propene intermediate. On the other hand, P-Bi203 revealed a direct propane conversion into acrolein without having to go through propene route.